Wide field spectrograph concepts for the European extremely large telescope - art. no. 62692G - Moretto, G; Bacon, R; Cuby, J; Hammer, F; Amram, P; Blais-Ouellette, S; Blanc, P; Devriendt, J; Epinat, B; Fusco, T; Jagourel, P; Hernandez, O; et al. (2006)
We report on the science case high level specifications for a wide field spectrograph instrument for an Extremely Large Telescope (ELT) and present possible concepts. Preliminary designs are presented which resort to different instrument concepts: monolithic integral field (IFU), multi-IFU, and a smart tunable filter. This work is part of the activities performed in the work package 'Instrumentation' of the 'ELT Design Study', a programme supported by the European Community, Framework Programme 6.